ISOLASI BAKTERI PROTEOLITIK AIR BUDIDAYA IKAN DAN KEMAMPUANNYA DALAM HIDROLISIS PROTEIN - , ARIFA ZUCHROTUNNISA, Dr. Ir. Ngadiman, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Proteolytic bacteria is a group ofbacteria that play role in degrading protein and could be used in decreasing protein in aquaculture pond. This research was aimed to obtain isolates of proteolytic bacteria thathave high capability in hydrolyzing protein from aquaculture ponds. Sources of the bacteria were sludge and water mixture of milkfish, shrimp, african catfish, and giant gouramy aquaculture ponds. The proteolytic bacteria were isolated by pour plating on skim milk agar medium. Qualitative selection was based on hydrolysis zone in the skim milk agar medium, and quantitative selection was done by Lowry method. Morphological and physiological tests were also observed to determine the isolates characters. In vitrotest on natural media was assayed to know proteolytic activity of the selected isolates. Eighty four proteolytic bacteria were isolated from the samples among them, sixteenisolates were selected having specific enzyme activity 1,76 - 20,196 unit/mg protein. The selected isolates have various morphological and physiological characters. Introduction of the selected isolates in aquaculture water of milkfish, shrimp, giant gouramy, and african catfish could increase the protein degradation rate 35, 36, 25, and 55 %.